2020
DOI: 10.1038/s42003-020-01471-6
|View full text |Cite
|
Sign up to set email alerts
|

Complimentary action of structured and unstructured domains of epsin supports clathrin-mediated endocytosis at high tension

Abstract: Membrane tension plays an inhibitory role in clathrin-mediated endocytosis (CME) by impeding the transition of flat plasma membrane to hemispherical clathrin-coated structures (CCSs). Membrane tension also impedes the transition of hemispherical domes to omega-shaped CCSs. However, CME is not completely halted in cells under high tension conditions. Here we find that epsin, a membrane bending protein which inserts its N-terminus H0 helix into lipid bilayer, supports flat-to-dome transition of a CCS and stabili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 76 publications
(126 reference statements)
0
14
0
Order By: Relevance
“…In these acquisitions, the total internal reflection of the excitation beam creates an evanescent field that illuminates the lateral regions of CPs at a higher intensity compared to the apex, which is further away from the glass substrate. As a result, formation of CPs is marked by a characteristic “ring” pattern (100–200 nm in diameter) under super-resolution imaging ( Li et al, 2015 ; Joseph et al, 2020 ; Willy et al, 2021b ) ( Figures 1A,B ). Reducing the excitation NA (i.e., incidence angle of the excitation beam) enables increasing the penetration depth of the illumination field, i.e., approaching the structured illumination microscopy at the grazing incidence mode (GI-SIM), and imaging deeper inside cultured cells and fruit fly embryos with enhanced spatiotemporal resolution ( Guo et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these acquisitions, the total internal reflection of the excitation beam creates an evanescent field that illuminates the lateral regions of CPs at a higher intensity compared to the apex, which is further away from the glass substrate. As a result, formation of CPs is marked by a characteristic “ring” pattern (100–200 nm in diameter) under super-resolution imaging ( Li et al, 2015 ; Joseph et al, 2020 ; Willy et al, 2021b ) ( Figures 1A,B ). Reducing the excitation NA (i.e., incidence angle of the excitation beam) enables increasing the penetration depth of the illumination field, i.e., approaching the structured illumination microscopy at the grazing incidence mode (GI-SIM), and imaging deeper inside cultured cells and fruit fly embryos with enhanced spatiotemporal resolution ( Guo et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Increased membrane tension reduces the initiation density ( Ferguson et al, 2017 ), and slows down the growth and dissolution rates of endocytic clathrin-coated structures ( Ferguson et al, 2016 ). Moreover, internalization of CPs from the plasma membrane becomes dependent on the curvature generating adaptor proteins ( Joseph et al, 2020 ; Willy et al, 2021a ) and the forces provided by actin polymerization under increased tension ( Boulant et al, 2011 ; Jin et al, 2022 ; Kaplan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Caveolin-1 redistributes to the upstream edge of ECs subjected to HSS [ 67 ]. Thus, HSS might lead to a translocation of Caveolin-1 to areas of high mechanical tension which impedes internalization via CvME [ 68 ]. In support of this, it was observed that an increase in membrane tension, induced by mechanical stress, leads to rapid disassembly of caveolae in human cells [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another way to generate membrane curvature is by inserting a protein segment into the bilayer (wedging), 6 a mechanism that has been shown to co-operate to stabilize hemispherical clathrincoated structures. 7 Oligomerization and crowding at large con-centrations, resulting from curvature-mediated forces, 8 can also cause or increase membrane bending. 4,6,[9][10][11] Synthetic molecules that stably interact with the lipid bilayer can have important remodeling effects, as well.…”
mentioning
confidence: 99%